Regulable multichannel generator of pulses imitating scintillation flashes of tungstates - V. V. Kobychev (Âderna Fìzika ta Energetika, 2007)
Simple unit for generation of pulses with time parameters similar to those of scintillation flashes of tungstates is described. Amplitudes and delay time of the pulses are regulable. The generator allows creating up to four independent pulses in the separate channels, their sum (direct or inverted) as well as trigger pulses synchronized to the leading edge of every pulse. The generator is intended for adjustment of complicate data acquisition systems for detectors based on the tungstate scintillators.